Self-regulated learning strategies among ESL and TESL students in UNIMAS - Saw, Lee Wei. (Universiti Malaysia Sarawak, UNIMAS, 2007)
This study explored the self-regulated learning strategies used by the English-as-a-second-language (ESL) and teach - English - as - a - second - language (TESL) students in Universiti Malaysia Sarawak. The purpose s of t his study are to investigate w hat self - regulated learning strategies are preferred and non - preferred by ESL and TESL students, what demograp hic characteristics (gender, age , and course ) have determined on the choice of self - reg ulated learning strategies, and which self - regulated learni ng strategies has influenced the achievement (CGPA) of ESL and TESL students in UNIMAS. Sixty - nine ESL students and one hundred and thirteen TESL students participated in this study. This study used survey design and data was collected using the Motivated Strategies for Learning Questionnaire (MSLQ). The analysis showed that cognitive learning strategy (M=3 .68) was most frequently used self - regulated learning strategy by the ESL and TESL students , both the male and female students, from the age groups of 15 - 24, 25 - 34, and 35 - 44. T ime and study environment management strategy (M=3.38) was the least frequently used self - regulated learning strategy by the male and female students from the age groups of 25 - 34 and 35 - 44. F emale students and ESL students used more self - regulated learning strategies than male students and TESL students. G ender did show different favor in using self - regula ted learning strategies. Besides, there were significant differences (p> .05) in self - regulated learning strategies between the ag e groups. Students with different CGPA did show different favor in using self - regulated learning strategies. Implications and suggestions for further research were put forward.